Barriers to Uptake of Postpartum Long-Acting Reversible Contraception: Qualitative Study of the Perspectives of Ugandan Health Workers and Potential Clients - Willcox, Merlin; King, Emma; Fall, Emma; Mubangizi, Vincent; Nkalubo, Julius; Natukunda, Silvia; Nahabwe, Haeven; Goodhart, Clare; Graffy, Jonathan (Studies in family planning, 2019)
Health workers have received training on delivering postpartum long-acting reversible contraceptives (LARCs) through several projects in Uganda, yet uptake still remains poor. To understand the reasons, and to gather suggestions for improving uptake, we conducted individual semi-structured interviews with a total of 80 postpartumparents, antenatal parents, health workers, and village health teams in rural south-westUganda. Interviews were recorded, transcribed, translated, and analyzed using qualitative thematic analysis. Specific barriers to uptake of immediate postpartum contraception for women included: the need to discuss this option with their husband, the belief that time is needed to recover before insertion of a LARC, and fear that the baby might not survive. Furthermore, social consequences of side-effects are more serious in low-income settings. Suggestions for improving uptake of postpartum contraception included health education by “expert users,” couples counseling during antenatal care, and improved management of side-effects
Keywords: Postpartum; Contraception; Ugandan Health Workers; Potential Clients